Single-session ureteroscopic pneumatic lithotripsy for the management of bilateral ureteric stones - Isen,Kenan (2012)
PURPOSE: In nowadays there is no consensus on single-session ureteroscopic lithotripsy (URSL) for the management of bilateral ureteric stones. The aim of this study was to evaluate efficacy and safety of single-session URSL in patients with bilateral ureteric stones. MATERIALS AND METHODS: 41 patients who have undergone bilateral single-session URSL were evaluted in this study. A 8/9.8 Fr Wolf semi-rigid ureteroscope was used for the procedures, and the stones were fragmented with pneumatic lithotripter. RESULTS: A high stone-free rate was achieved (90.2%) after single endoscopic procedure with a retreatment rate of 9.8%. The procedure was most successful for distal ureteric stones with a 96.2% stone-free rate followed by middle ureteric stones with a 81.8% stone-free rate while the least success was achieved for proximal ureteric stones with a 77.7% stone-free rate (p < 0.05). A greater stone-free rate was obtained in those with stones less than 10 mm (93.7%) than in those with stones larger than 10 mm (77.7%) (p < 0.05). Ureteral perforation occurred in only one patient (2.4 %). No long-term complication was observed in any patient. CONCLUSIONS: Bilateral single-session URSL can be performed effectively and safely with a low complication rate in patients with bilateral ureteric stones. It can reduce the need of anaesthetics and hospital stay.